Efficacy of Difenoconazole Emulsifiable Concentrate with Ionic Liquids against Cucumbers Powdery Mildew - Qingrong Peng; Fengmao Liu; Chunrong Zhang (International Journal of Chemical Engineering)
Among eight ionic liquids (ILs) examined, 1-n-butyl-4-methyl-pyridinium bromide (BMPyBr,  5) was used in this study as an appropriate alternative to benzene homologs and derivatives to be used in 10 wt% water-insoluble difenoconazole emulsifiable concentrate (EC). Moreover, 10 wt% difenoconazole EC with BMPyBr (5) exhibited the same efficacy as 10 wt% difenoconazole wettable powder (WP) against powdery mildew on cucumbers under field conditions. The results revealed that difenoconazole EC with BMPyBr (5) had excellent stability at 268 K and 327 K after 14 days through high-performance liquid chromatography (HPLC). Therefore, ILs can be considered as promising environment-friendly adjuvants for pesticides that are commercially processed as EC formulation.